PH-dependent fluorescence of thiol-coated CdSe/CdS quantum dots in an aqueous phase. (24th November 2020) - Lesiak, Anna; Banski, Mateusz; Halicka, Kinga; Cabaj, Joanna; Żak, Andrzej; Podhorodecki, Artur
Abstract: The results presented in this paper show how the optical properties and colloidal stability of quantum dots (QDs) vary depending on pH conditions. For this investigation, as-synthesized hydrophobic CdSe/CdS QDs were transferred to an aqueous medium by surface modification with 3-mercaptopropionic acid. The ligand exchange procedure was applied under three different pH conditions: acidic, neutral and alkaline, to obtain three kinds of hydrophilic QDs dispersed in phosphate buffer. The efficiency of the functionalization of QDs was estimated based on the changes in ABS and the highest value was obtained under acidic conditions (45%). The efficiency of photoluminescence (PL) was also best preserved under these conditions, although it was 30 times less than the PL of hydrophobic QDs. Then, all three kinds of hydrophilic QDs were dispersed in solutions with a wide range of pH (2–12) and investigated by absorbance and PL measurements. The results show that QDs subjected to a ligand exchange procedure are characterized by intensive PL at the selected pH values, which correspond to pKa of the ligand. This phenomenon is independent of the pH at which the ligand exchange procedure is conducted. Moreover, it was found that the PL intensity is preserved during the experiment for QDs functionalized under neutral conditions, whereas it decreases for acidic and increases for alkaline conditions.